TANGGAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS PADA PEMBERIAN MIKROORGANISME BERMANFAAT DAN KOMPOS TANDAN KOSONG KELAPA SAWIT - Reyza Kurniawan; Ratna Rosanty lahay; Sanggam Silitonga,; Chairani Hanum (Jurnal Agroekoteknologi, 2014)
Development of sweet corn culture technique need efficient of farming system, more economical,quality, and productivity. For this reason, research has been conducted at experimental field of USUAgriculture Faculty (± 25 m asl.) in July – October 2013 using a randomized block design with twofactors. The first factor was concentrations of microorganism with levels: 0, 10, 20, and 30 ml/l ofwater, were the second factor was doses of Empty Fruit Bunches Oil Palm (EFBOP) compost withlevels: 0, 150, and 300 g per plant with three replications. The result of this research showed thatapplication of microorganism had significant effect on plant height at six’th weeks after planting(WAP), cob with husk per plant, and cob without husk per plant. Empty fruit bunches oil palmcompost significant effect only for stem diameter. Interaction between application microorganismand EFBOP compost significant effect on cob length and cob diameter.Keywords : sweet corn, beneficial microorganisms, EFBOP compost